Simulation Modeling of Technological Processes of Logging - Konstantin P. Rukomojnikov; Tatiana V. Sergeeva; Tatiana A. Gilyazova; Evgeny М. Tsarev; Vera P. Komisar (Лесной журнал)
The history of the development of simulation modeling in the field of operation of forest felling machines is described, the main leaders in the development of computer support systems for managerial decision-making are named, and the advantages and disadvantages of various approaches to simulation modeling of the production process in the forest are listed. The aim of the research has been to evaluate achievements in this field and find ways to increase their effectiveness and improvement. It has been noted that the simulation approach eliminates fluctuations in results due to uncontrollable factors such as operator exposure and weather conditions, and rare non-cyclical working elements and delays of various types can be excluded from the simulation model. This facilitates comparison of the performance of alternative machine systems and technologies under ideal conditions. The conducted review makes it possible to focus the attention of scientists on the lack of knowledge of the functioning of machines for felling trees in conditions of non-continuous logging; the need to increase the number of analyzed factors that improve the accuracy of modeling; maximum use in models of modern technological recommendations for the work of forest machine operators; the importance of creating mathematical dependencies taking into account factors affecting labour efficiency. It has been concluded that the existing models are promising, but still leave a large field for further modernization and new research. The review clearly demonstrates a significant increase in the number of analyzed indicators of the natural production process in simulation modeling compared to mathematical one and a reduction in labour and material costs compared to the research of technological processes in production conditions. Simulation modeling of machine felling allows taking into account the influence of random environmental factors, as well as factors of interaction between logging equipment. The widespread introduction of such computer systems in timber harvesting will increase the efficiency of technological maps for the development of forest plots and the substantiation of standard machine performance indicators.